Olympic quadrennial planning: Psychological keys for maximizing performance and minimizing distractions at the Olympic Games - Cohen, A. (Olympic & Paralympic Coach, 2014)
Multiple factors contribute to a successful Games experience. The foundation of performance excellence clearly begins with capable athletes and effective coaching- facilitated by a four-year (or longer) plan for maximizing performance in the Olympic Games setting. A quadrennial High Performance Plan should outline a pathway for success at the Games by identifying realistic performance markers to be incrementally accomplished along a progressive trajectory - with the goal of achieving specific performance metrics at the Olympic Games. While there are many similarities between Olympic Trials, World Championships and the Olympic Games, there are many aspects of the Games environment that are entirely unique and require special preparation. This article examines some of these characteristics with a focus on psychological preparation for maximizing performance at the Olympics. Issues related to pre-Games preparation and Games-specific challenges are addressed. Anticipating and planning for potential obstacles will allow your athletes to focus on simple keys that maximize opportunities for performance excellence.